2021
DOI: 10.1073/pnas.2024576118
|View full text |Cite
|
Sign up to set email alerts
|

CAP1 binds and activates adenylyl cyclase in mammalian cells

Abstract: CAP1 (Cyclase-Associated Protein 1) is highly conserved in evolution. Originally identified in yeast as a bifunctional protein involved in Ras-adenylyl cyclase and F-actin dynamics regulation, the adenylyl cyclase component seems to be lost in mammalian cells. Prompted by our recent identification of the Ras-like small GTPase Rap1 as a GTP-independent but geranylgeranyl-specific partner for CAP1, we hypothesized that CAP1-Rap1, similar to CAP-Ras-cyclase in yeast, might play a critical role in cAMP dynamics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Similar to CAP1-Δ471-474, CAP1-Δ1-35, CAP1-PP1mut, and CAP1-WH2mut normalized MRTF-SRF signaling in CAP1-KO neurons. CAP1-Δ1-35 specifically lacked OD together with two RLE repeats relevant for modulation of Gα S -stimulated adenylyl cyclase activity ( 28 , 49 ). Instead, CAP1-PP1mut is impaired in interaction with profilin or SH3 domain proteins such as tyrosine kinase ABL1 ( 27 , 50 52 ), and mutation of CAP1’s WH2 domain (CAP1-WH2mut) abolished binding ability to adenosine 5′-triphosphate (ATP)–G-actin ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CAP1-Δ471-474, CAP1-Δ1-35, CAP1-PP1mut, and CAP1-WH2mut normalized MRTF-SRF signaling in CAP1-KO neurons. CAP1-Δ1-35 specifically lacked OD together with two RLE repeats relevant for modulation of Gα S -stimulated adenylyl cyclase activity ( 28 , 49 ). Instead, CAP1-PP1mut is impaired in interaction with profilin or SH3 domain proteins such as tyrosine kinase ABL1 ( 27 , 50 52 ), and mutation of CAP1’s WH2 domain (CAP1-WH2mut) abolished binding ability to adenosine 5′-triphosphate (ATP)–G-actin ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CAP1-Δ471-474, CAP1-Δ1-35 as well as CAP1-PP1mut normalized MRTF localization and SRF activity in CAP1-KO neurons. CAP1-Δ1-35 specifically lacked OD together with two RLE motifs, which are necessary for both adenylyl cyclase binding and positive modulation of GαS-stimulated adenylyl cyclase activity in mammals (Zhang et al, 2021;Rust and Marcello, 2022), and CAP1-PP1mut is impaired in interaction with the ABP profilin or SH3 domain proteins such actin-binding protein 1 (ABP1) or tyrosine kinase ABL1 (Freeman et al, 1996;Bertling et al, 2007, Balcer, 2003Rust et al, 2020). We therefore concluded that CAP1 oligomerization, its stimulatory function towards adenylyl cyclase as well as its interaction with profilin, ABP1 or ABL1 were not important for neuronal MRTF-SRF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions were stopped in trichloroacetic acid (7.5% w/v). Product [ 3 H]-cAMP was separated from the substrate [ 3 H]-ATP by sequential column chromatography over Dowex and Alumina, as previously described 75 .…”
Section: Methodsmentioning
confidence: 99%